2021
DOI: 10.1111/febs.15768
|View full text |Cite
|
Sign up to set email alerts
|

Critically evaluating sweet taste receptor expression and signaling through a molecular pharmacology lens

Abstract: The class C G protein-coupled sweet taste receptor (STR) is responsible for the perception of sweet-tasting molecules. Considered an obligate heterodimer, it consists of taste 1 receptor 2 and taste 1 receptor 3 subunits. Interest in the STR has steadily grown, especially since its discovery in extraoral tissues hints at a metabolic role for the receptor. It is now known that many pharmacologically exploitable binding sites exist across the extracellular and transmembrane regions of both subunits of the STR, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 77 publications
1
18
0
Order By: Relevance
“…This suggests that heterozygosity is sufficient for the SNP effect on HbA 1c . In contrast, the rs9701796 (Ser9Cys) polymorphism of TAS1R2 , which has comparable allele frequency to Ile191Val ( 17 ), had no associations with HbA 1c ( Table 2 and Figures 1C,D ). No genotype differences were noted in OGTT variables or in insulin sensitivity or pancreatic beta-cell responsiveness during a FSIVGTT ( Table 2 ).…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…This suggests that heterozygosity is sufficient for the SNP effect on HbA 1c . In contrast, the rs9701796 (Ser9Cys) polymorphism of TAS1R2 , which has comparable allele frequency to Ile191Val ( 17 ), had no associations with HbA 1c ( Table 2 and Figures 1C,D ). No genotype differences were noted in OGTT variables or in insulin sensitivity or pancreatic beta-cell responsiveness during a FSIVGTT ( Table 2 ).…”
Section: Resultsmentioning
confidence: 95%
“…amino acid) ( 25 ). Out of the nine TAS1R2 nonsynonymous SNPs, the rs35874116 (Ile191Val) and rs9701796 (Cys9Ser) have a minor allele frequency >0.2 and are associated with different nutritional and metabolic variables ( 17 ). TAS1R2 -(Ile191Val) in particular is associated with sugar and carbohydrate consumption in adults ( 11 , 13 ) and in children ( 12 ), but these effects are not due to differences in taste sensitivity ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the allele frequencies of most missense variants in the translated region of TAS1R2 are low (<10%), but the rs9701796 allele (Ser9Cys) is comparable to Ile191Val [ 23 ]. This substitution is located in the putative signal peptide of TAS1R2 and has also been associated with dietary and anthropometric variables in children [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…Using genetic and pharmacological approaches, we previously showed that fructose potentiates insulin secretion dependent on STR and the activation of a PLC signaling cascade [ 9 ]. However, similar to other GPCRs, there is evidence suggesting that STR may have diverse signaling partners depending on the ligand and cell context [ 10 ]. Therefore, we set to investigate whether saccharin-induced insulin secretion is dependent on STR and elucidate the signaling mechanism.…”
Section: Introductionmentioning
confidence: 99%